2010
DOI: 10.1590/s0100-29452010005000063
|View full text |Cite
|
Sign up to set email alerts
|

Controle de tortricídeos em macieira com duas formulações de Bacillus thuringiensis var. Kustaki em Fraiburgo-SC

Abstract: RESUMO -Grapholita molesta e Bonagota cranaodes são duas importantes pragas de pomares de macieira controlada por inseticidas. O objetivo deste estudo foi testar duas formulações de Bacillus thuringiensis var. kurstaki (Btk) para o controle desses tortricídeos. Parcelas de macieira 'Fuji' foram pulverizadas com Dipel PM e Dipel SC, nas concentrações de 100 mL por100 L de calda. A eficiência do Btk foi comparada com os inseticidas tebufenozide (Mimic 240 SC -90 ml por 100 L) e clorpyrifos (Lorsban 480 BR -150 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Unfortunately, this pest control management resulted in harmful outcomes such as the selection of resistant populations of insect pests, compromising the efficiency of control and forcing farmers to use increasingly high doses of pesticides [2][3][4]. Moreover, these chemical insecticides have harmful effects on human health and wildlife, leaving residues in food and the environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this pest control management resulted in harmful outcomes such as the selection of resistant populations of insect pests, compromising the efficiency of control and forcing farmers to use increasingly high doses of pesticides [2][3][4]. Moreover, these chemical insecticides have harmful effects on human health and wildlife, leaving residues in food and the environment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the B. thuringiensis-based insecticide, which acts on ingestion, a greater action was expected in reducing fruit borer symptoms because, theoretically, there would be sufficient time for caterpillar contamination when scraping fruit peel before penetration. Monteiro & Souza (2010) demonstrated that B. thuringiensis var. kurstaki-based formulations are as efficient as tebufenozide-and chlorpyrifos-based chemical products for controlling Grapholita molesta (Busck) and Bonagota cranaodes (Meyrick) (Lepidoptera: Tortricidae) in the apple tree.…”
Section: Efficacy Of Insecticides To Control Cerconota Anonellamentioning
confidence: 99%
“…In Brazil, Btk is used for the control of Grapholita molesta (BUSCK, 1916) (Lepidoptera: Tortricidae), in apple trees (MONTEIRO and SOUZA, 2010), whose action affects other lepidoptera that occur simultaneously such as apple leafroller Bonagota salubricola (MEYRICK, 1937) (Lepidoptera: Tortricidae) (MONTEIRO and SOUZA, 2010).…”
Section: Introductionmentioning
confidence: 99%